Math, asked by rohansahutelukala, 11 months ago

(3+5√6)(4+4√8) simplify​

Answers

Answered by raj3294
1

Answer:

Step-by-step explanation:

(3+5√6)(4+4√8)

USING DISTRIBUTIVE PROPERTY:

(A+B)(C+D) = (A*C+A*D+B*C+B*D)

= 3*4+3*4√8+5√6*4+5√6*4√8

= 12+12√8+20√6+20√48

= 12(1+√8)+20(√6+√48)       √8 = 2.8,√6 = 2.4,√48 = 6.9.

= 12(1+2.8)+20(2.4+6.9)

= 12*3.8+20*9.3

= 45.6+186

= 231.6.

HOPE THIS HELPS.

Answered by Anonymous
0

(3+5√6)(4+4√8)

=3(4+4√8)+5√6(4+4√8)

=(12+12*2√2)+(20√6+20*√6*2√2)

=12+24√2+20√6+80√3

Similar questions